FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PEMERINTAH DI PROVINSI ACEH - Win, admin; Irne (IndOmera, 2022)
This research aims to analyze the factors that influence financial performance in Aceh Province. The data used in this study was sourced from the APBD budget realization report in 23 regency/cities in Aceh Province with period of 2010-2017, so that it has a balance panel data with a total of 184 observations. This research used static panel data by used the assumption is multiple regression analysis. The results of this research indicade that capital expenditure has positive and significant effect on financial permormance, general allocation fund have positive and significant effect on financial permormance, special allocation fund have negative and significant effect on financial permormance, economic growth has no effect significant and negative on financial permormance. And special autonomy fund has negative and significant effect on the financial performance of local government regency/cities in Aceh Province. The government should prioritize capital expenditure budget for the public interest, so that a more independent region is created